2003
DOI: 10.1080/0028825x.2003.9512841
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an allopolyploid complex in New ZealandPolystichum(Dryopteridaceae)

Abstract: Evidence is provided for the first demonstrated example of allopolyploidy in the New Zealand fern flora. Cytological, morphological, and molecular (AFLP-DNA fingerprinting) analyses indicate that the fern previously known as Polystichum richardii constitutes an allopolyploid complex, in which four separate evolutionary lineages are present. These are here recognised as three taxonomic species, with one of these encompassing two subspecies. The two allooctoploid lineages are accommodated under the reinstated na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 50 publications
2
43
0
1
Order By: Relevance
“…Scatter-plots were used to assess which pairs of quantitative morphological characters exhibited concordant partitioning, where the samples are more or less restricted to two diagonally opposite quadrants of the graph. Perrie et al (2003a) considered that two independent characters were only likely to show concordant partitioning if two separate lineages, or assortatively fertilising groups of individuals, were present.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Scatter-plots were used to assess which pairs of quantitative morphological characters exhibited concordant partitioning, where the samples are more or less restricted to two diagonally opposite quadrants of the graph. Perrie et al (2003a) considered that two independent characters were only likely to show concordant partitioning if two separate lineages, or assortatively fertilising groups of individuals, were present.…”
Section: Methodsmentioning
confidence: 99%
“…Following the approach of Perrie et al (2003a), we test the null hypothesis that P. vestitum sens. lat.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, octoploids share multiple chloroplast types with each other and their progenitors, indicating repeated polyploidisation events (A. gracillimum, A. cimmeriorum (Perrie & Brownsey 2005b)). Allopolyploidy in New Zealand ferns has also been documented using molecular approaches vnPolystichum, where P. neozelandicum is an allo-octoploid of the tetraploids P. wawranum and P. oculatum (Perrie et al 2003). Chloroplast sequences indicate that the tetraploid Hypolepis ambiguamay be composed of independently derived allopolyploid lineages of unknown parentage (Perrie & Brownsey unpubl.…”
Section: Hybrid Speciesmentioning
confidence: 99%
“…gracillimum has inferred parents^, bulbiferum andA. hookerianum; Perrie & Brownsey 2005a;Shepherd et al 2008a); 2% P olystichum neozelandicum (inferred parentage P. wawranum and P. oculatum; Perrie et al 2003);…”
Section: Species Conceptsmentioning
confidence: 99%
“…Both of these large genera include patterns of reticulate speciation that have been the focus of recent molecular studies, e.g. Schneider et al (2012), Dyer et al (2012), and Chang et al (2013) on Asplenium and Perrie et al (2003) on Polystichum. Schneider and colleagues' (2012) study of Asplenium using two low-copy nuclear markers plus ITS found conflict between the markers that they interpreted as evidence of ancient reticulation events.…”
Section: Dryopteris In Asiamentioning
confidence: 99%